A Novel Rotor Topology for High-Performance Fractional Slot Concentrated Winding Interior Permanent Magnet Machine - Dutta, Rukmi; Pouramin, Alireza; Rahman, Muhammed F. (IEEE transactions on energy conversion, 2021)
This article presents a finite-element-based, multiobjective design optimization study of the fractional-slot, concentrated wound, permanent magnet synchronous machine (FSCW PMSM). Design objectives included maximization of efficiency, minimization of cost and low ripple without sacrificing torque density and wide constant power speed range. A large-scale optimization study revealed that while a V-type rotor provides high torque density, a spoke-type rotor has the benefit of low torque ripple. Quest for a design that can combine the goodness of both V- and spoke type rotors for an FSCW stator has led to a novel interior permanent magnet rotor topology referred here as Y-type. The goals of achieving maximum efficiency, minimum cost and wide CPSR were also accomplished in the proposed Y-type FSCW IPMSM. For experimental verification purpose, three fully optimized rotors - V-, spoke- and Y-type were constructed for a 12-slot/10-pole FSCW stator. Extensive experimental tests were conducted on three machines for a detailed comparison study. It will be shown that the proposed Y-type FSCW IPMSM outperforms both V and spoke-type configurations. A scaled-up version of the Y-type FSCW IPMSM shown to have satisfied many of the Freeedomcar 2020 targets, which is promising for application in electric vehicles.